2019
DOI: 10.1002/jaba.618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a trial‐based interview‐informed synthesized contingency analysis

Abstract: We evaluated the viability of an interview-informed synthesized-contingency analysis (IISCA) conducted in a trial-based format with 3 children with autism spectrum disorders who engaged in problem behavior. We compared results to those from typical trial-based and traditional functional analyses and found high degrees of correspondence. The trial-based IISCA format took the least amount of time to conduct and was associated with the lowest frequencies of problem behavior. Results are discussed in terms of meri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Similar comparisons were conducted by Greer et al (2020) with eight additional participants, Curtis et al (2020) with three participants, and Holehan et al (2020) with five additional participants. Synthesized-contingency analyses yielded a differentiated outcome for each participant, but interaction effects were once again ruled out by identifying sensitivity to reinforcement under isolated-contingency test conditions.…”
Section: Discriminant Validitymentioning
confidence: 90%
“…Similar comparisons were conducted by Greer et al (2020) with eight additional participants, Curtis et al (2020) with three participants, and Holehan et al (2020) with five additional participants. Synthesized-contingency analyses yielded a differentiated outcome for each participant, but interaction effects were once again ruled out by identifying sensitivity to reinforcement under isolated-contingency test conditions.…”
Section: Discriminant Validitymentioning
confidence: 90%
“…Walter's and Phillip's FAs were conducted as part of a previously published study (Curtis et al, 2020) that evaluated outcomes of several FA variations, including traditional (procedures similar to Iwata, Dorsey, Slifer, Bauman, and Richman[1982, 1994]), modified trial‐based (procedures based on Bloom, Lambert, Dayton, & Samaha, 2013), and combined trial‐based and synthesized‐contingency analyses (Hanley, Jin, Vanselow, & Hanratty, 2014). Given that the traditional‐FA format is the most precise and experimentally rigorous of the three FA formats, our treatment was informed by results from the traditional FA, which indicated that both Walter's and Phillip's problem behaviors were multiply maintained by attention, tangibles, and escape.…”
Section: Methodsmentioning
confidence: 99%
“…The clinician repeated these steps in various arrangements to gain a better understanding of the evocative properties of the events that occasion problem behavior. The procedures of the brief contingency probe shares many similarities with the trial‐based IISCA that presents 20 trials of a synthesized establishing operation during the test segment and compares problem behavior to that of a control segment when the synthesized reinforcers are available (Curtis et al, 2020). The core differences being that the brief contingency probe (a) only presents a few trials, (b) is complete after problem behavior is consistently evoked, and (c) the contingency evaluated can shift unsystematically based on the participant's performance and in situ caregiver feedback.…”
Section: Methodsmentioning
confidence: 99%